Dokumentacja zdarzeń gospodarczych w rachunkowości rolniczej - Markiewicz, Dominika (Economic Events Documentation in Agricultural Accounting, 2005)
Changing market conditions especially Poland’s entry to European Union cause growth of importance of the agricultural accounting as well as reliable economic events documentation.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1073, s. 29-34